Adaptacja studentów zagranicznych na uczelniach jako główne wyzwanie edukacji migracyjnej w Polsce - Kozula , Magdalena (Kultura-Społeczeństwo-Edukacja, 2018)
The aim of this article is to show the broaden perspective on actions taken by universities in the area of adaptation and the influence of adaptation and language programs on the further performance of international students in the academic environment. What does influence the process of acculturation and how is it correlated with the ability to learn and work in the receiving society? The paper concludes with a few reflections on the role of how the adaptation program should be seen by the universities and why is it important for education of foreigners.